Vigna radiata (L.) R. Wilczek Extract Inhibits Influenza A Virus by Targeting Viral Attachment, Penetration, Assembly, and Release - Lo, Chieh-Wen; Pi, Chia-Chen; Chen, You-Ting; Chen, Hui-Wen (Frontiers in Pharmacology, 2020)
Vigna radiata (L.) R. Wilczek (mung bean) is a Chinese functional food with antioxidant, antimicrobial and anti-inflammatory activities. However, little is known about its antiviral activity. We aimed to investigate the antiviral activity and mechanisms of action of Vigna radiata extract (VRE) against influenza virus. HPLC was conducted to analyzed the components of the VRE. The anti-influenza viral activity of VRE in MDCK cells was evaluated by virus titration assays, hemagglutination assays, quantitative RT-PCR assays, cellular α-glucosidase activity assays and neuraminidase activity assays. Chromatographic profiling analysis identified two major flavonoids, vitexin and isovitexin, in the ethanol extract of Vigna radiata. Through in vitro studies, we showed that VRE, at concentrations up to 2000 μg/mL, exhibited no cytotoxicity in MDCK cells. VRE protected cells from influenza virus-induced cytopathic effects and significantly inhibited viral replication in a dose-dependent manner. A detailed time-of-addition assay revealed that VRE may act on both the early and late stages of the viral life cycle. We demonstrated that 1) VRE inhibits virus entry by directly blocking the HA protein of influenza virus; 2) VRE inhibits virus entry by directly binding to cellular receptors; 3) VRE inhibits virus penetration; 4) VRE inhibits virus assembly by blocking cellular α-glucosidase activity, thus reducing HA protein trafficking to the cell surface; and 5) VRE inhibits virus release by inhibiting viral neuraminidase activity. In summary, Vigna radiata extract potently interferes with two different subtypes of influenza virus at multiple steps during the infectious cycle, demonstrating its broad-spectrum potential as an anti-influenza preventive and therapeutic agent. Continued development of Vigna radiata-derived products into antiviral therapeutics is warranted.